Determinantes do desenvolvimento na primeira infância no Brasil - Ricardo Paes de Barros; Lisa Biron; Mirela de Carvalho; Mariana Fandinho; Samuel Franco; Rosane Mendonça; Andrezza Rosalém; André Scofano; Roberta Tomas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The progress occurred over the last decade is undeniable, combining less poverty, with more choice and access to better services, as well as better use of these services by families with children. However, more important than the speed of progress may be the fact that it was clearly equalizing. Not only the mortality and malnutrition have declined, but access and use the wide range of services expanded more among children in families with high vulnerability than those not vulnerable. Also declined the differences between rural and urban areas, and between the North and Northeast regions on the one hand, and South and Southeast, on the other. But despite this substantial progress, the situation of early childhood in the country still requires considerable attention. Ensure these children basic living conditions and opportunities necessary for their development is and will remain, one of the biggest challenges for the coming decades. Success will require continued progress. However, continuity of results does not necessarily mean further action. It is essential that public policies meet new challenges and that actions directed for areas where progress has been relatively slow be strengthened. In particular, we must pay special attention to reducing neonatal mortality, promotion of exclusive breastfeeding, the expansion of access to basic sanitation and the reduction in the proportion of children without birth registration. Overcome these challenges, we have guaranteed minimally adequate basic care for infants.
Keywords: I32; I38; I39; 330